A low RCS microstrip antenna based on a composite technology of slotting and loading split‐rings. Issue 11 (17th August 2022) - Jiakai, Zhang; Yabing, Yang; Anqi, Wu; Jiaocheng, Zhao
Abstract: This study proposes a method to reduce the wideband radar cross‐section (RCS) of a microstrip antenna while maintaining its dimensions. Modifications to the design of the antenna consist of patch slotting, ground slotting, and coplanar split‐ring loading without changing its size. The results of simulations show that a significant reduction in the RCS can be obtained in the range of frequency of 1–3 GHz. The maximum in‐band RCS and out‐of‐band RCS are 20.8 and 38 dB, respectively. Prototypes of the reference antenna and the proposed composite antenna are manufactured and tested, and the results are consistent with those of the simulation.